Potentialities of neem in pest management - Pandey, Rakesh; Vibha, Vibha (Indian Farming, 2015)
Increasing awareness towards ecofriendly approaches, the neem and its products are gaining wider acceptability to their utilization. The bio-efficacy of neem seed kernel extract on various insect-pests has already been established. It was further studied that the kernels of ully ripened fruits alone exhibit the highest insecticidal potency. Therefore, neem can be considered as an integral component of the future sustainable IPM programmes.